REGULATING INITIAL COIN OFFERING AMIDST THE DEVELOPMENT OF CRYPTO ASSETS IN INDONESIA - Fira Natasha; Muhammad Akbar; Harryandi, Alexander (Bank Indonesia, 2022)
In the era of digital economic development, blockchain and crypto asset innovations have gained wide acceptance and skyrocketing worldwide demand. Behind the emergence of popular crypto assets, the mechanism of an Initial Coin Offering (ICO) is used to issue this new form of currency. An ICO is highly favoured because of its efficiency, minimum underwriting requirements, high profits, and liquidity. Without exception, the hype accompanying ICOs has also influenced the Indonesian public. There remains, however, very minimal protection for investors who participate in ICOs that are being held in Indonesia. There are many disadvantages to an ICO, including high risks for investors, its vulnerability to fraud or crime, and the lack of regulation regarding the mechanism of ICOs. Furthermore, ICOs are very much intertwined with the development of decentralised finance (DeFi), one of the latest crypto-related financial innovations. DeFi likewise poses various risks and threats to the traditional financial system that needs to be monitored from the beginning of the ICO process. Therefore, by using normative research methods based on literature studies, this study aims to comprehensively explain the problems of ICO investor protection in Indonesia and the solutions for overcoming these problems.